Large energy-storage density and positive electrocaloric effect in xBiFeO3–(1 − x)BaTiO3 relaxor ferroelectric ceramics. Issue 4 (4th January 2022) - Tang, Hui; Niu, Xiang; Zhao, Peng-Fei; Tang, Xin-Gui; Jian, Xiao-Dong; Chen, Xian-Yi; Peng, Xiao-Cao; Yang, Zhi-Peng; Lu, Sheng-Guo
Abstract : Large energy storage density and big electrocaloric strength in the BiFeO3 –BaTiO3 system. Abstract : x BiFeO3 –(1 − x )BaTiO3 relaxor ferroelectric ceramics were synthesized via the high-temperature solid-state reaction process. The X-ray diffraction patterns of x BiFeO3 –(1 − x )BaTiO3 showed that the structure of samples was transformed from the tetragonal phase to the pseudo-cubic phase when x ≥ 0.025. The calculated universal Curie–Weiss constants and slim shape of the polarization-electric field hysteresis loops indicated that x BiFeO3 –(1 − x )BaTiO3 ceramic was converted from a normal ferroelectric to a relaxor ferroelectric. The energy-storage properties of 0.1BiFeO3 –0.9BaTiO3 were also measured at room temperature. The maximum discharged energy density and efficiency procured were 1.22 J cm −3 and 85.98%, respectively. The electric field-dependent energy-storage density was fitted using an exponential function of E n, and it was found that n < 2. It was worth noting that the positive electrocaloric effect (ECE) was observed in x BiFeO3 –(1 − x )BaTiO3 bulk ceramics, no matter when directly measured using a thermocouple or indirectly calculated using the Maxwell relation. Also, a Δ T max of 1.55 K was indirectly calculated from the temperature-dependent P–E hysteresis loops for 0.05BiFeO3 –0.95BaTiO3 ; while a Δ T max of 2.20 K was directly obtained using the thermocouple. The positive ECE means that the x BiFeO3 –(1 − x )BaTiO3 is a conventional ferroelectric or relaxor ferroelectric. Finally, the electrocaloric strengths measured were considered with the equation d T /d E obtained by Lu et al.